Enhanced Electrochemical Sensing with Carbon Nanotubes Modified with Bismuth and Magnetic Nanoparticles in a Lab‐on‐a‐Chip. Issue 9 (25th July 2016) - Jothimuthu, Preetha; Hsu, Joe L.; Chen, Robert; Inayathullah, Mohammed; Pothineni, Venkata Raveendra; Jan, Antony; Gurtner, Geoffrey C.; Rajadas, Jayakumar; Nicolls, Mark R.
Abstract: Iron plays an especially important role in human physiological functions and pathological impairments. The superior properties of carbon nanotubes (CNTs) and their modification with bismuth and magnetic nanoparticles as developed in this work have led to an extraordinary and novel material to facilitate ultrasensitive detection in the nanomolar range. Here, we present the development of an electrochemical sensor for detection of ferrous (Fe 2+ ) and ferric (Fe 3+ ) iron by means of CNTs modified with bismuth and magnetic nanoparticles for higher sensitivity of detection. The sensor fabrication includes microfabrication methodologies, soft lithography, and electrodeposition. Cyclic voltammetry and differential pulse voltammetry are used for the electroanalytical studies and detection of the ions in samples. The sensor has a dynamic range of detection from 0.01 nm to 10 mm . The performance of the sensor with modified CNTs was explored for sensitivity and specificity. CNTs, modified with bismuth and magnetic nanoparticles by means of electrodeposition, enhanced the detection limit significantly down to 0.01 nm . Abstract : Ferreting out ferrous and ferric : An extraordinary and novel electrochemical sensor material detects ferrous (Fe 2+ ) and ferric (Fe 3+ ) iron by means of CNTs modified with bismuth and magnetic nanoparticles for ultrahigh detection sensitivity. The differential pulse voltammetry (DPV) results of the sensor show a dynamic range of detection from 0.01 nm to 10 mm .